Nature of manganese species in Ce1-xMnxO2-delta solid solutions synthesized by the solution combustion route - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, V. (Chemistry of Materials, 2005)
A series of manganese-cerium oxide composites with Mn concentrations in the range of 1-20 mol % in ceria was prepared by the solution combustion technique using urea as fuel. The nature, type, and oxidation state of Mn species in ceria were investigated by X-ray diffraction (XRD), diffuse reflectance UV-visible spectroscopy, electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy, and temperature-programmed reduction techniques. The study reveals that the method of preparation significantly influences the type of manganese species in ceria. Wet-impregnation, coprecipitation, and solid-state synthesis techniques lead to clustered MnOx-like species in the ceria matrix, while the present method of preparation (solution combustion route) yields a highly dispersed form of Mn species. In the reported series of samples, Mn is present mainly in +2 and +3 oxidation states and there is no evidence for the presence of Mn 41 species. Powder X-ray diffraction studies at variable temperatures (298-1323 K) indicate the formation of Ce1-xMnxO2-delta Solid solutions. No separate MnOx-type phase was detected even at 1323 K. EPR studies reveal that the isolated Mn2+ and Mn2+ species are present in at least three different structural locations: species A, Mn ions in ceria-lattice defect sites; species B, Mn ions in framework Ce4+ locations; and species C, Mn ions in interstitial locations and at the surface of ceria. The Mn3+ ions in ceria exhibit a facile reduction and reoxidation behavior when exposed to dry hydrogen and subsequently to air at elevated. temperatures. A highly dispersed state of Mn3+ and Mn2+ in ceria, facile redox behavior, and a synergistic Mn-ceria interaction are some of the unique properties of this material prepared by the solution combustion procedure.

Epoxidation of indene and cyclooctene on nanocrystalline anatase titania catalyst - Ramaswamy, Veda; Awati, Preeti; Ramaswamy, A. V. (Topics in Catalysis, 2006)
Nanocrystalline anatase titania samples of different crystallite sizes were prepared by sol gel method using ultrasonication and calcination at different temperatures. The calcined samples were treated with H2O2 in order to study the role of surface hydroxyl groups present on titania in generating reactive oxygen species responsible for the epoxidation reaction. The crystallite size of the calcined samples increased from 4 to 18 nm as the calcination temperature increased from 473 to 773 K, respectively. More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline TiO2 by using ultrasonication. EPR spectral data on the H2O2-treated samples confirmed the presence of superoxide radical species. The two distinct UV bands observed at 400 and 450 nm are assigned to charge transfer of peroxide (O-2 2-) to Ti. FT-IR spectral data show that the surface hydroxyl groups are the active sites in the generation of reactive oxygen species. The catalytic activity was evaluated in a series of epoxidation reactions using indene and cyclooctene as substrates and aqueous H2O2 as oxidant. The activity was found to decrease with increase in the calcination temperature of the samples, obviously due to an increase in crystallite size and a decrease in surface hydroxyl groups. The nanoparticle titania samples show better conversion and selectivity than the standard titania (Degussa P-25). The kinetic studies revealed that the reaction followed a pseudo first order kinetics in excess of H2O2.
Keywords: cyclooctene epoxidation; epoxidation of indene; nanocrystalline anatase titania; superoxide radical on titania

Au-Pt nanoparticles in amine functionalized MCM-41: catalytic evaluation in hydrogenation reactions - Joseph, Trissa; Kumar, K. Vijay; Ramaswamy, A. V.; Halligudi, Shivaraj B. (Catalysis Communications, 2007)
Nano-sized Au-Pt nanoparticles (Au-Pt-bi-MNPs) have been synthesized by the simultaneous reduction of HAuCl4 and HPtCl6 by NaBH4 inside the channels of amine functionalized Si-MCM-41 (NH2-Si-MCM-41) at ambient conditions. These materials were characterized using chemical analysis, UV-vis, XPS, XRD, FT-IR, Surface area and TEM analysis. The size of these alloyed nanoparticles (bi-MNPs) were found in the range of 2-4 nm. These nanoparticles were evaluated to study their catalytic activities towards hydrogenation of aromatic nitro compounds. The catalytic activity of the Au-Pt bi-MNPs was found to be superior to monometallic An nanoparticles. (c) 2006 Published by Elsevier B.V.
Keywords: amine-functionalized MCM-41; Au-Pt nanoparticles; Catalytic hydrogenation

Direct hydrothermal synthesis of mesoporous Sn-SBA-15 materials under weak acidic conditions - Shah, P.; Ramaswamy, A. V.; Lazar, Karoly; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2007)
A direct synthetic route for the preparation of Sn-SBA-15 materials with n(Si)/n(Sn), ratios ranging from 100 to 10 under milder acidic conditions than normally employed for the preparation of Si-SBA-15 is reported. The changes in the pH conditions of the gel were made through an adjustment of the molar ratio of n(H2O) to n(HCl) (< 1 pH < 2) during preparation. The samples prepared under three different acidic conditions have been characterized by various techniques. An expansion of the lattice (powder XRD) and an increase in mesopore area (low temperature N-2 adsorption) indicate that the hexagonal structure of the SBA- 15 is maintained with no loss of long range ordering. The UV-vis reflectance spectra of Sn-SBA-15 samples show the presence of Sn4+ ions both in tetrahedral and octahedral environment. Si-29 MAS NMR spectra of samples prepared under an intermediate acid condition show the presence Of Q(3) and Q(4) species. Their ratio increases with a decrease in tin content. The presence of Si in (2Si, 2Sn) i.e., Q(2) environment may point to incorporation of considerable Sn4+ ions in tetrahedral positions. Sn-Mossbauer spectroscopic studies reveal that Sn2+ species form upon reductive treatments and can probably be stabilized in the pore wall upon reoxidation. This to some extent is an indication of the formation and stabilization of Si-O-Sn-O-Si linkages in Sn-SBA-15. A progressive increase in the pH of the medium (increasing the n(H2O) to n(HCl), ratio) results in the location of Sn4+ ions, (a) at the surface of the mesopores (surface of the corona region) as a thin film of SnO2 or small aggregates (loss in mesopore area) depending on the concentration of Sn; (b) at the walls of the mesopore structure, substituting Si4+ ions (some lattice expansion and tetrahedral Sn4+ ions); and/or (c) as a part of the corona region, neutralizing the resulting Si-OH groups (a loss of micropore area and octahedral Sn4+ ions). The studies reveal that the method of preparation, n(H2O)/n(HCl) ratio and the n(Si)/n(Sn) ratio (concentration of SnCl4) of the gel significantly influence the type of tin species in the resulting Sn-SBA-15 samples. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: direct synthesis of Sn-SBA-15; Si-29 and Sn-119 MAS-NMR; Sn-mossbauer spectroscopic studies; Sn-SBA-15; tin-mesoporous silica

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

Synthesis, characterization and catalytic activity of Sn-SBA-15 mesoporous molecular sieves - Ramaswamy, Veda; Shah, Pallavi; Lazar, Karoly; Ramaswamy, A. V. (Catalysis Surveys from Asia, 2008)
Our recent reports on the synthesis of Sn-incorporated mesoporous SBA-15 materials have been reviewed. The preparation of the samples with different Si/Sn ratios followed two procedures, the first is the post-synthesis modification of SBA-15 by impregnation with Sn chloride or acetate, and the second is the direct method in which Sn chloride was introduced in to Si precursor along with amphiphilic triblock copolymer, while varying the ratio of the synthesis gel. Detailed characterization of the Sn-SBA-15 samples by a variety of techniques shows how the synthesis procedures influence the properties of the samples that reflect on the differences in (a) the structural features, (b) morphology and textural properties, such as the pore characteristics, (c) the possible location of Sn4+ ions in the meso silica structure and their reducibility, (d) the nature of the Sn species and their the coordination sphere and (e) the acid-base characteristics. We developed a possible model for the localization of Sn species in SBA-15 pore structure for different conditions of preparation. This report includes our investigations on the catalytic properties of these Sn-SBA-15 samples in 3 industrially important reactions, viz., trans-esterification of diethyl malonate, synthesis of nopol by Prins condensation of beta-pinene with para-formaldehyde and the epoxidation of norbornene. In each of this reaction, while demonstrating the catalytic role of Sn species, we show that the requirement of the type and the environment of Sn species are different for these reactions.
Keywords: mesoporous materials; Properties of Sn-SBA-15; Sn-containing SBA-15; Sn-SBA-15 catalysts; Synthesis of Sn-SBA-15

Special Issue dedicated to Paul Ratnasamy on the occasion of his 70th birthday preface - Reddy, Benjaram M.; Sivasanker, S.; Ramaswamy, A. V. (Catalysis Today, 2012)